Atmospheric corrosion of copper exposed to different environments in the region of Valparaiso, Chile. Issue 3 (6th September 2016) - Vera, R.; Araya, R.; Bagnara, M.; Díaz‐Gómez, A.; Ossandón, S.
Abstract : This article presents the results obtained for the atmospheric corrosion of copper after 3 years of exposure at different sites within the region of Valparaiso, Chile. Frames were installed with samples at seven sites located close to the coast and inland. They were accompanied by devices to measure atmospheric chloride and sulphur dioxide content and weather stations to obtain data on temperature, humidity, amount of rainfall and wind speed. The results show a correlation between corrosion rate and the environmental and meteorological conditions in the area, and with the morphology and electrochemical properties of the corrosion product formed on the copper surface. The sites gave corrosivity categories of C5, C4, C3 and C2. The behaviour of corrosion rate was modelled using power function models and neural networks. The main corrosion products were cuprite, posnjankite, covelite and atacamite. Abstract : The behaviour of copper with respect to atmospheric corrosion was analysed at seven sites within the fifth region of Chile. The corrosivity category order was: Quintero (C5) > Casablanca, Curauma (C4) > Valparaiso, Los Andes, Rio Blanco (C3) > Quilpué (C2). Posnjankite (Cu4 (SO4 )(OH)6  · H2 O), cuprite (Cu2 O) and covelite (CuS) were found in the corrosion products formed on the copper samples, irrespective of the different atmospheres.